Efficacy of Non Invasive Ventilation Techniques in Acute Respiratory Failure (Journal of Advances and Scholarly Researches in Allied Education, 2025)
One of the leading causes of hospitalization, illness, and mortality globally is acute respiratory failure (ARF). One of the major causes of chronic obstructive pulmonary disease (COPD) is acute exacerbations, which provide a significant barrier to therapy. Improving patient outcomes while reducing the need for intrusive mechanical breathing requires effective management methods, such as non-invasive ventilation (NIV). The purpose of this research was to compare the effectiveness of conventional treatment for ARF caused by AECOPD with that of non-invasive ventilation administered via a portable device. Seventy patients hospitalized to Saudi Arabia's Buraidah Central Hospital with ARF as a result of AECOPD were the subjects of a prospective cohort research. One group of patients received standard treatment, whereas the other group received NIPPV, or non-invasive positive pressure breathing. While mortality rate, co-morbidities, length of stay in the intensive care unit, and longevity of NIV usage were secondary objectives, NIPPV failure was the major result. The patients' average age was 61.08, and 86% of them were men. The success rate of the NIPPV group was 74%, which was significantly greater than the conventional treatment group's rate of 54%. The leading cause of NIPPV failure was deteriorating arterial blood gases (33%), whereas the most common consequence was face skin abrasion (17%). Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients who are experiencing acute respiratory failure may benefit from NIV as a first-line treatment. It is already an essential part of ARF therapy, and its link to reduced mortality, fewer intubation rates, and quicker acidosis correction just adds to that.